The dialectic of the intercourse and the female's lack of consent elements in the crime of rape in Bahraini law: A comparative study - Al-Sayed, Manal (Journal of Legal Sciences, 2023)
The crime of rape is based on three pillars, the objective pillar which is the act of intercourse, the victim’s lack of consent pillar, and the subjective pillar, which is in the form of criminal intent, and since rape is an intentional crime, there is stability in the legal trend on its content, which is the knowledge of the perpetrator and his willingness to sexually assault the victim without consent.However, there are many controversial issues regarding the act of sexual assault and the lack of the victim’s consent which are studied in this article.  As the difference in the definition of sexual intercourse leads to the exclusion of many acts from the concept of the crime of rape, such as the difference in what is meant by sexual intercourse, the used tool, and the part of the victim’s body being assaulted. Such factors can make an act a crime of rape in one legal system, while it is not in others, which necessitates the study of these issues and the comparison of provisions to reach the optimal rules for this crime. In addition, the element of the victim’s lack of consent is linked to several factors that lead to a difference in the legal ruling, such as the age at which the victim’s consent is disregarded, and the application of aggravating circumstances when the perpetrator exploits the victim mental illness.  Moreover, the female may reverse her consent during intercourse.In addition, many laws, especially Western ones, have made amendments to the husband’s coercion of his wife to have sexual intercourse, while the prevailing trend was that such an act is a man’s right, which is still consistent with the trend of most countries that apply Islamic Sharia.  After studying the two pillars of rape, we reached several conclusions, namely the importance of expanding the judiciary’s definition of rape to extend to anal sexual intercourse, amending Article 344 of the Bahraini Penal Code to include the definition of rape annal sexual assault on a male, and to consider the perpetrator’s exploitation of the mental disability of the victim within the aggravated cases provided for in Article 348, and amending Article 345 by making the age at which consent is not considered eighteen years instead of twenty-one.